CORRIGENDUM: Regulation in the sphere of circulation of extemporaneously compounded medicines under modern conditions of Russia [. Pharmacy & Pharmacology. 2024;12(5):324-337. DOI: 10.19163/10.19163/2307-9266-2024-12-5-324-337] - V. V. Ryazhenov; E. A. Maksimkina; V. S. Fisenko; A. V. Alekhin; V. V. Tarasov; M. G. Raisyan; E. R. Zakharochkina; K. A. Chizhov; R. Yu. Garankina (Фармация и фармакология (Пятигорск), 2025)
Referred to by: Ryazhenov V.V., Maksimkina E.A., Fisenko V.S., Alekhin A.V., Tarasov V.V., Raisyan M.G., Zakharochkina E.R., Chizhov K.A., Garankina R.Yu. Regulation in the sphere of circulation of extemporaneously compounded medicines under modern conditions of Russia. Pharmacy & Pharmacology. 2024;12(5):324-337. https://doi.org/10.19163/2307-9266-2024-12-5-324-337 We hereby inform readers that in the final version of the article changes were made in Russian and English.In the published article " Regulation in the sphere of circulation of extemporaneously compounded medicines under modern conditions of Russia", the authors found an error: accidentally, due to a technical error on part and without any malicious intent, еhe regulatory document was incorrectly specified in table 1 (p.330):Resolution of the Government of the Russian Federation No. 546 “On Approval of the Regulations on Licensing of Pharmaceutical Activities” dated March 31, 2022.The authors regret that, due to an oversight, the cited regulatory document was incorrectly numbered (No. 546)  in the originally published version of this article.Correct version:Resolution of the Government of the Russian Federation No. 547 “On Approval of the Regulations on Licensing of Pharmaceutical Activities” dated March 31, 2022. The error occurred due to the fault of the entire team of authors, but does not change the essence of the data presented in the article, does not violate their perception by readers or interpretation.The authors would like to apologize for any inconvenience. The authors declare no conflict of interest.The original article has been updated in online-version:  https://www.pharmpharm.ru/jour/article/view/1664